(untitled) - Vernon, Ursula (New York, New York, 2015)
Never a conventional princess, Harriet becomes an adventurer after learning she's cursed to fall into a deep sleep on her twelfth birthday, but after two years of slaying ogres, cliff-diving, and more with her riding quail Mumfrey, things go awry at home and she must seek a prince to set things right.
Keywords: Blessing and cursing; Fiction; Blessing and cursing; Fiction; Humorous Stories; Fiction; Hamsters; Adventure and adventurers; Adventure stories; Princesses; Juvenile fiction; Hamsters; Juvenile fiction; Juvenile fiction; Princesses; Fiction